2016
DOI: 10.1590/1807-3107bor-2016.vol30.0067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of new innovative restorative carbomised glass cement on intrapulpal temperature rise: an ex-vivo study

Abstract: Effect of new innovative restorative carbomised glass cement on intrapulpal temperature rise: an ex-vivo study Abstract: This study aimed to evaluate the temperature changes that occurred in the pulp chamber when using GCP Glass Carbomer Fill (GCP) and two different resin-modified glass-ionomer (RGI) restorative materials at different dentin thicknesses. A standardized Class I occlusal cavity with 1 mm or 2 mm dentin thickness was prepared in the extracted human molar teeth. RGI and GCP fills were placed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
1
10
0
4
Order By: Relevance
“…Introduced materials include high-viscosity glass ionomer cements (HVGICs), resin-modified glass ionomer cements, self-adhesive resin cements, glass carbomer (GC) cements, and bulk-fill composite (BC) resins. [ 3 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Introduced materials include high-viscosity glass ionomer cements (HVGICs), resin-modified glass ionomer cements, self-adhesive resin cements, glass carbomer (GC) cements, and bulk-fill composite (BC) resins. [ 3 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Water circulation was previously introduced in the experimental design in an attempt to simulate pulpal microcirculation and its cooling effect [12,13,15]. However, it is not determined to what extent the experimental water circulation is clinically relevant in mimicking the actual pulpal microcirculation effects on heat dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of the temperature rise in the pulp chamber during restorative procedures pointed to the contributing factors such as the remaining dentin thickness [11][12][13], type of the restorative material [11,[13][14][15][16][17], type of LCU [16,18,19], curing times [19,20] and distances [21]. It was also reported that an experimental setup involving simulated microcirculation in the pulp chamber resulted in a lower temperature rise [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Ca10 (PO 4 ) 6 (OH) 2 ] [5,6]. HAp has excellent biocompatibility, and both its composition and chemical composition are similar to dental structure and bone tissue [7].…”
Section: Introductionmentioning
confidence: 99%